Design of Oxygen‐doped Co3S4 Hollow Nanosheets by Suppressed Sulfurization for Supercapacitors. Issue 19 (16th August 2021) - Zhang, Xu; Tian, Yuhan; Lu, Wang; Yang, Shixuan; Qu, Ning; Zhang, Qiang; Lei, Da; Liu, Anmin
Abstract: Cobalt sulfides can be considered as auspicious electrode materials for supercapacitors due to the good electrical conductivity and high reversible redox capability. In this study, the O‐doped Co3 S4 hollow nanosheets supported on carbon paper (O−Co3 S4 /CP) are facilely prepared through a suppressed sulfurization method by using CP‐supported Co‐ZIF as the precursor and methanol as the solvent. The hollow nanosheets not only offer fast transport pathways but also provide abundant redox active sites. Furthermore, theoretical calculations indicate that the O doping can enhance the adsorption ability of OH − on O−Co3 S4 with electrochemical activity and electrical conductivity improvement. Owing to the advantages of the appropriate composition and unique structure, the as‐made hollow structure O−Co3 S4 /CP shows a remarkable specific capacitance of 755 F g −1 at a current density of 1 A g −1, while a good rate performance of 65 % capacitance retention at 10 A g −1 can be reached. Moreover, the asymmetric supercapacitors assembled by O−Co3 S4 /CP and activated carbon electrodes yield an energy density of 21.3 Wh kg −1 with power density of 0.75 kW kg −1 . The present work can offer a useful guidance for the exploitation of O doped cobalt sulfides hollow nanosheets for supercapacitors. Abstract : O−Co3 S4 hollow nanosheets supported on carbon paper have been successfully fabricated by suppressed sulfurization method, which exhibit good electrochemical performance.